Cambridge Vocabulary for IELTS classroom vocabulary practice - Cullen P. Pauline (Cambridge Books for Cambridge Exams)
Are you preparing for the IELTS test? Do you want to practise all the vocabulary you need to be confident in the test? Cambridge Vocabulary for IELTS covers the vocabulary that occurs in the test and provides the following: error warnings to help you avoid common mistakes regular tests to check your progress practice exam tasks from the Academic and General Training Reading, Writing and Listening papers, useful tips on how to approach exam tasks techniques for learning and remembering vocabulary a full wordlist for easy reference vocabulary in a listening context. Cambridge Vocabulary for IELTS is informed by the Cambridge International Corpus and the Cambridge Learner Corpus to ensure that vocabulary is presented in genuine contexts and the book covers the errors students really make.